Promising Antineoplastic Actions of Melatonin - Favero, Gaia; Moretti, Enrico; Bonomini, Francesca; Reiter, Russel J.; Rodella, Luigi Fabrizio; Rezzani, Rita (Frontiers in Pharmacology, 2018)
Melatonin is an endogenous indoleamine with an incredible variety of properties and activities. In recent years, an increasing number of studies have investigated this indoleamine’s interaction with cancerous cells. In particular, it seems that melatonin not only has the ability to improve the efficacy of many drugs used in chemotherapy but also has a direct inhibitory action on neoplastic cells. Many publications underlined the ability of melatonin to suppress the proliferation of various cancer cells or to modulate the expression of membrane receptors on these cells, thereby reducing tumor aggressiveness to metastasize. In addition, while melatonin has antiapoptotic actions in normal cells, in many cancer cells it has proapoptotic effects; these dichotomous actions have gained the interest of researchers. The increasing focus on melatonin in the field of oncology and the growing number of studies on this topic require a deep understanding of what we already know about the antineoplastic actions of melatonin. This information would be of value for potential use of melatonin against neoplastic diseases.